Strategi Pembelajaran di Era Digital: Gamifikasi dan Metode Inkuiri dalam Meningkatkan Belajar Siswa Sekolah Dasar - Taufik Afandi; Abdul Khobir; Muhlisin Muhlisin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The digital era requires the world of education to adapt to learning innovations that can increase student participation and enthusiasm, especially at the elementary school level. This research was motivated by students' low interest in learning which was influenced by conventional learning methods that were less interactive. The aim of this research is to examine the effectiveness of creative learning strategies through collaboration between gamification and inquiry methods in increasing student enthusiasm for learning. This research uses a qualitative approach with a case study method carried out in one elementary school in Indonesia. Data was collected through observation, interviews and documentation, then analyzed descriptively. The research results show that the integration of gamification with inquiry methods can significantly increase students' active involvement, curiosity and enthusiasm for learning in the learning process. The use of game elements combined with independent exploration is proven to create a fun and challenging learning atmosphere. The implications of these findings show the importance of implementing innovative and contextual learning strategies to support student learning processes in the digital era. This strategy is recommended as an alternative learning method that is relevant to be widely implemented in elementary schools.